MQMAS spectra of half-integer quadrupolar nuclei enhanced by indirect DNP - Hiroki Nagashima; Julien Trébosc; Olivier Lafon; Jean-Paul Amoureux (Journal of Magnetic Resonance Open)
The observation of half-integer quadrupolar nuclei, which represent 66 % of the NMR-active isotopes, is essential to understand the atomic-level structure of inorganic materials near the surfaces with applications in the field of catalysis, biomaterials and optoelectronics. For that purpose, we have recently introduced an efficient technique, which combines the sensitivity gain provided by indirect DNP (dynamic nuclear polarization) under MAS (magic-angle spinning) and the high resolution obtained by refocusing the second-order quadrupolar interaction (H. Nagashima et al., J. Phys. Chem. Lett. 15 (2024) 4858). This technique combines (i) a D-RINEPT (dipolar-mediated refocused INEPT) transfer, (ii) an MQMAS (multiple-quantum MAS) filter, and (iii) a QCPMG (quadrupolar Carr-Purcell Meiboom-Gill) detection. We explain the design of several variants of this pulse sequence and notably the selection of the coherence transfer pathways. In particular, the amplitudes of the coherence transfer pathways through the ±3Q coherence orders of the quadrupolar isotope can be equalized using a train of π-pulses selective of the central transition, instead of a z-filter. This equalization method has the advantage to limit the length of the phase cycles and to enhance slightly the signal intensity. Moreover, for spin-3/2 nuclei subject to moderate or large quadrupolar interactions, more efficient excitation and conversion of 3Q coherences are achieved using cosine-modulated long-pulses (cos-lp), instead of fast-amplitude-modulated (FAM) pulses. The performances of the different D-RINEPT-MQMAS-QCPMG variants are compared through the observation of 35Cl and 27Al isotopes without DNP in l-histidine hydrochloride and isopropylamine-templated microporous aluminophosphate (ipa-AlPO4–14), respectively, as well as the acquisition of DNP-enhanced high-resolution spectra of 11B and 17O nuclei near the surface of partially oxidized boron nitride supported on dendritic and fibrous nanosilica and γ-alumina enriched in 17O isotope using a slurrying approach. The spectra recorded for γ-alumina show that the slurrying method produces less disorder than grinding assisted by 17O-enriched water.